University educators’ perceptions about Artificial Intelligence in education - González González, Sandra Jazmin (2024)
The present study addresses the integration of Artificial Intelligence (AI) in higher education from the perspective of university professors. Its realization responds to the urgent need to understand the attitudes and perceptions of these professionals in light of the increasing presence of AI in the educational field, a trend that is reshaping the way teaching and learning are conducted. The objectives of the research are to thoroughly explore teachers' attitudes toward AI in education and to propose specific recommendations for its effective and ethical use. A qualiquantitative observational perception methodology was employed, collecting data through digital surveys administered to 93 professors from various higher education institutions in the southern region of Ecuador. This methodology provided a detailed insight into the experiences and opinions of the teachers. The study's results highlight a high familiarity among teachers with AI and a significant interest in its implementation to personalize learning and improve educational outcomes. However, significant concerns also emerge, such as the risk of academic dishonesty, where students might use AI to cheat, and the potential loss of personal interaction between teachers and students, which is essential for students' holistic development. By addressing these concerns and promoting an informed and participatory adoption of AI, it is possible to ensure that its integration into the educational field maximizes its benefits and minimizes its risks.